La mobilité internationale à destination de la France - Marie-Claude Muñoz (Les éditions de la Maison des sciences de l'Homme, 2009)
Scientific exchanges facilitate the international mobility of Brazilian scholars while contributing at the same time to the diffusion of knowledge. This article presents the results of a qualitative survey of Brazilian state fellows engaged in doctorate, doctorate-sandwich and post-doctorate studies in human and social sciences in France. It analyses the factors behind international mobility (social capital and academic training) and the cost involved therein, on the one hand, the concrete unfolding of the training period in France and the use upon return in Brazil of the knowledge thus acquired, on the other hand. The interviews reveal the complex interrelationships between objective and subjective factors aside from informing us on the processes at the roots of the choices of those concerned and on the perspectives created by international mobility of scholars.